New flavonoids with multiple bronchodilator activity pathways from Tephrosia purpurea L. (Pers.) growing in Saudi Arabia - Maged S. Abdel-Kader; Abdulaziz S. Saeedan; Najeeb U. Rehman; Hayder M. Faqihi; Gamal A. Soliman (Elsevier, 2024)
Total extract of Tephrosia purpurea (T. purpurea) expressed potent ex-vivo bronchodilator effect in isolated Guinea pigs' tracheal muscles. Fractionation of T. purpurea total extract (TPTE) using liquid-liquid technique followed by ex-vivo bronchodilator testing indicated that the activity was trapped to the chloroform (CHCl3) soluble fraction. Phytochemical study of the CHCl3 fraction guided by ex-vivo bronchodilator activity led to the isolation of 7 active flavones of which compounds 1 (epi-Tephroapollin G), 3 (Acetyltephroapollin C), 4 (4''-Dehydroxytephroapollin E), and 5 (epi-Tephroapollin F) were new. Structures were identified using relevant spectroscopic tools including optical rotations and CD data. Compounds 1, 3, 4 and lanceolatin A (6) behaved like papaverine by inhibiting carbachol (CCh) as well as high potassium (K+)-mediated contractions at equivalent concentrations with varied potencies whereas (-)-Tephroapollin G (2) selectively inhibited CCh-mediated contractions but was not found active against high K+. epi-Tephroapollin F (5) and (-)-Pseudosemiglabrin (7) in contrast were significantly more potent to abolish CCh induced contraction when compared with high K+ similar to dicyclomine. Papaverine like dual phosphodiesterase enzyme Ca++ ion inhibitory activities of 1, 3, 4 and 6 were confirmed indirectly by the bolster of the isoprenaline curves against CCh to the left whereas Ca++ inhibitory effect of 1 and 3-7 was confirmed by the rightward deflection of Ca++ concentration-response curves (CRCs) towards right with quashing of the maximum response in same fashion like verapamil. Moreover, compounds 2, 5 and 7 at lower concentrations showed selective blockade of muscarinic receptor similar to atropine. Oral administration of the TPTE, CHCl3 and 7 to guinea pigs significantly protected against bronchospasm induced by 0.2 % histamine aerosol in vivo.